PENGELOLAAN PRODUK PISANG LOKAL ROID JATIGEDE DI KELOMPOK TANI GIRI MEKAR DAN KELOMPOK GENERASI MUDA BINARAJA MILLENNIALSS SMART FARMING (BMSF) DI DESA MEKARASIH KECAMATAN JATIGEDE: PENGELOLAAN PRODUK PISANG LOKAL ROID JATIGEDE DI KELOMPOK TANI GIRI MEKAR DAN KELOMPOK GENERASI MUDA BINARAJA MILLENNIALSS SMART FARMING (BMSF) DI DESA MEKARASIH KECAMATAN JATIGEDE - Ade Ismail; Rifat Fadhilah; Meddy Rachmadi; Cecep Odim; Yuli Sitanawati (PT. RANESS MEDIA RANCAGE, 2023)
Mekarasih Village is a village located in the Jatigede sub-district of Sumedang Regency. In Mekarasih Village there is a millennials generation that can be developed to increase the potential in Mekarasih Village. Mekarasih Village has a superior commodity of Roid banana, and local products that have the potential to be developed, namely Denana Chips banana chips and Roid J chips. However, the products produced are still relatively simple in terms of packaging and do not have an adequate marketing strategy. Therefore, to improve the quality of local product potential, product development is needed to increase sales of banana chips owned by Mekarasih Village, so that it can have an impact on improving the village economy. The activities that will be carried out in this Village Project program are Identification of superior banana seed sources as basic raw materials for planting, Structuring and grouping of millennials young generations, Identifying the front land of high school from pest and disease attacks, Structuring Product Management, Marketing, publication, and Promotion of Binaraja Millennialss. Through a series of village project activities, young millennialss are increasingly broadening their horizons and are expected to help unleash their potential in agriculture, and local products.